Revision of the Australian leaf beetle genus Cheiloxena Baly, 1860 (Coleoptera: Chrysomelidae: Spilopyrinae) - Reid, C. A. M.; Beatson, M. (Zootaxa, 2018)
The endemic Australian leaf beetle genus Cheiloxena Baly, 1860 is revised, with eight valid species, three new: C. aitori sp. nov.; C. blackburni Reid, 1992; C. conani sp. nov.; C. frenchae Blackburn, 1893; C. insignis Blackburn, 1896; C. monga sp. nov.; C. tuberosa Reid, 1992; C. westwoodii Baly, 1860. A key is provided for their identification and all species are described. Cheiloxena species occur from southern Victoria to central Queensland. Hosts are Araliaceae (Astrotricha), Proteaceae (Lomatia) and possibly Myrtaceae (Eucalyptus).